Addressing nutritional gaps and suggesting a practical framework to reduce the risk of malnutrition and improve nutrition security in santhal tribal communities in India - Armes, S; Ayyad, S; Li, X; Nyaga, W; Banerjee, S; Bhanjdeo, A; Buckner, L; Chakraborty, D; Chakraborty, S; Kaur, H; Manna, A; Pattnaik, A; et al. (BMJ Publishing Group, 2023)
Background The double burden of malnutrition is a growing problem, which is disproportionately represented across the Indian population, with undernutrition dominating rural areas. This study aimed to identify nutritional gaps in traditional recipes of Santhal tribes, create a recipe book to address deficiencies and support diet diversity. Methods Food Frequency Questionnaires (FFQ) were conducted to analyse dietary patterns of Santhal communities. Recipes were collected from five villages and shortlisted into 37 dishes based on availability, acceptability and popularity. Commonly consumed templates were based on FFQ findings and individual dishes. Nutritics software was used to identify nutritional gaps. In total, 24 recommended templates, were created to satisfy adequate intake of nutrients. Mann-Whitney and unpaired t-test were performed and findings were presented as mean (standard deviation(SD)) and median (25th–75th percentile). Results Less than one-fifth of consumed templates met energy requirements, 27% met protein recommendations, and 4% met requirements for fibre, total fat, monounsaturated and polyunsaturated fat. Other nutrients of concern included vitamins B12, B9, iodine, calcium and iron. Recommended templates significantly increased energy (Consumed (C): 996.0kcal(930-1090); Recommended (R): 1183.0kcal(1094-1341); p<0.0001), protein (C: 25.0g(8.4); R: 40.5g(33.2-52.3); p<0.0001), total fat (C: 7.4g(6.1-8.8); R: 17.2g(14.1-22.9); p<0.0001) and fibre (C: 5.0g(4.0-6.5); R: 8.2g(5.8-11.7); p=0.0013) compared to consumed templates. Additionally, calcium (C: 108.5mg(36.0-302.5); R: 245.5mg(152.3-528.3); p=0.0121), iron (C: 5.3mg(2.1-8.2); R: 10.7mg(8.2-13.2); p=0.0002), vitamin B6 (C: 0.4mg(0.3-0.7); R: 1.1mg(0.6-1.6); p=0.0001), B9 (C: 54.5ug(36.3-172.8); R: 252ug(179.4); p=0.0026) and B12 (C: 0ug(0-0); R: 1.0ug(0-2.1); p=0.0001) were also significantly increased. Conclusion This study provides a novel insight on the nutritional adequacy of indigenous Santhal recipes and highlights the need to enhance the nutrition status of these communities. Concerted efforts should be made to increase communication for nutritional advocacy, both nationally and internationally. Future research should evaluate the acceptability, practicality, and uptake of this recipe book in addressing malnutrition in rural communities.